Copy list of queries from [Florence O'Donoghue] to Commandant J.J. O’Connell with replies, regarding the Easter Rising and countermanding orders in Cork, - O'Donoghue, Florence, 1895-1967
Details orders received to issue countermanding order and aftermath of the Rising, including his internment in Reading.